Differences associated with age at onset in early systemic sclerosis patients: a report from the EULAR Scleroderma Trials and Research Group (EUSTAR) database. (2nd January 2019) - Carreira, PE; Carmona, L; Joven, BE; Loza, E; Andréu, JL; Riemekasten, G; Vettori, S; Balbir-Gurman, A; Airò, P; Walker, U; Damjanov, N; Matucci-Cerinic, M; et al.
Abstract : Objective : The aim of this study was to analyse differences in clinical presentation in patients with early (< 3 years' duration) systemic sclerosis (SSc), comparing three age groups according to disease subsets. Method : Cross-sectional analysis of the prospective EULAR Scleroderma Trials and Research database (EUSTAR) was performed. Patients fulfilling preliminary American College of Rheumatology 1980 classification criteria for SSc, with < 3 years from the first non-Raynaud's SSc symptom at first entry, were selected. Patients with < 3 years from the first SSc symptom, including Raynaud's phenomenon, were also analysed. SSc-related variables, including antibodies, SSc subsets, and organ involvement, were examined. Age was categorized into ≤ 30, 31–59, and ≥ 60 years. We performed descriptive and bivariate analyses. Results : The study included 1027 patients: 90% Caucasian, 80% women, and 40% with diffuse disease. In early stages of SSc, younger patients had significantly more anti-Scl-70 antibodies and diffuse disease. With increasing age, we observed more elevation of estimated pulmonary systolic pressure on echocardiography (5%, 13%, and 30%, respectively, in the three age groups), cardiac conduction blocks (6%, 6%, and 15%), and left ventricular diastolic dysfunction (4%, 12%, and 27%). The results were similar for 650 patients with < 3 years from first SSc symptom, including Raynaud's. Conclusion : In early stages of SSc, older patients showed data indicating more severe disease with greater cardiac involvement. The diffuse subset was more frequent in the younger subgroup. The identification of such differences may help in selecting appropriate management for individual patients in clinical practice.